Measurement of nitric oxide concentration in a spark-ignition engine using degenerate four-wave mixing - Stevens, R; Ewart, P; Ma, H; Stone, C (2007)
The measurement of in-cylinder, combustion-generated nitric oxide using degenerate four-wave mixing (DFWM) in a firing, methane-fueled research engine is reported. An optical arrangement for producing DFWM in the forward geometry is described that results in reliable signal generation with excellent signal-to-noise ratio from the skip-fired engine. DFWM signals from temperature-insensitive lines were used to infer variations in NO concentration at the end of the expansion stroke at exhaust valve opening. The variation in NO concentration inferred from the DFWM signals was measured as a function of equivalence ratio and ignition timing indicated by peak pressure values. These measurements using DFWM were compared to measurements using line-of-sight optical absorption and a chemiluminescence exhaust gas analyzer. Good agreement was found for all three measurements. The results demonstrate the potential for DFWM to make quantitative spatially and temporally resolved measurements in a firing spark-ignition engine. © 2006 The Combustion Institute.